Unintended consequences of business digitalization among MSMEs during the COVID-19 pandemic: The case of Indonesia - Keita Oikawa; Fusanori Iwasaki; Yasuyuki Sawada; Shigehiro Shinozaki (Asian Development Bank (ADB), 2024)
The coronavirus disease (COVID-19) pandemic disrupted businesses, economies, and societies worldwide. This study employs unique data from Indonesia to investigate whether and how digitalization of micro, small, and medium-sized enterprises (MSMEs) helped them weather the adverse shocks from the pandemic and resulting lockdowns. The main empirical result is that, in the pandemic's early phases, digitalized MSMEs disproportionately encountered negative effects on their business outcomes. The seemingly harmful elements of digitalization disappeared during later stages. Moreover, COVID-19 restrictions initially had a "positive" impact on the business environment. This is counterintuitive. But when considering the panic buying at the onset of restrictions and large share held by the essential sector in our dataset, particularly the wholesale and retail sectors, the positive impact from the restrictions is not unreasonable. These findings suggest that the digital transformation had not yet been stably established among MSMEs by the start of the pandemic. Our findings provide critical implications for industrial and competition policies related to MSMEs during the COVID-19 recovery process.
Keywords: D22; G20; L20; L50; 330; digitalization; digital financial services; access to finance; SME development; SME policy; Indonesia